Los panos bolivianos en el imaginario cauchero (siglos XIX y XX) - Lorena I. Córdoba (Caravelle)
The article discusses the construction of social representations on the Panoan indigenous peoples of Bolivian Amazonia during the rubber boom (late 19th Century and early 20th Century). It is argued that this imagery was neither homogenous nor stable, and that the Pacaguara, Chacobo and Caripuna were portrayed in multiple ways by their observers.